Meningkatkan Kemampuan Berbahasa Anak Usia 5-6 Tahun Melalui Metode Read Alaud Di RA Persis 97 - Nurbaeti, Elmi Siti; Choiriyah , Choiriyah; Anggraeni, Rita Intan (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Elmi Siti Nurbaeti (1862050162). Enhancing Language Skills of Children Aged 5-6 Years Through the Read alaud Method at RA Persis 97 Cikajang Garut. Thesis. Bekasi: Universitas Panca Sakti Bekasi. 2024. his research aims to improve the language skills of children aged 5-6 years through the "Read Aloud" method at RA Persis 97. The research method used is Classroom Action Research (PTK) with the Kemmis and Taggart model which consists of four stages, namely planning, action, observation, and reflection. This research was conducted in two cycles, each consisting of four meetings. The results of this research showed an increase in children's language skills in each cycle. In the initial cycle, the percentage of children who reached the developing according to expectations (BSH) category increased from 48.65% to 60%. In cycle II, the percentage of children who reached the very well developed (BSB) category increased significantly to 81.92%. The research results show that the application of the "Read Aloud" method can significantly improve children's language skills, as seen from the increase in the average language ability score in each cycle. This research concludes that the "Read Aloud" method is effective as a language learning strategy in early childhood.